2021
DOI: 10.1371/journal.pone.0259946
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood development and urban environment in Mexico

Abstract: Background Childhood is considered the most important phase of human development; within it the period from birth to 5 years of age is particularly critical, given the speed at which changes occur. The context where children live can influence early childhood developmnent (ECD) by providing or limiting opportunities to learn, play and establish social interactions. This study explored the associations between characteristics of the urban environment and ECD in 2,194 children aged 36 to 59 months living in urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Such services include clinic outreaches, home visits, and ECD centres, which are positively associated with observed early childhood development. Research from elsewhere has indicated that the presence of ECD centres, healthcare and clinic services, and parental engagement programs is associated with higher odds of child development status (Minh et al, 2017;Prado-Galbarro et al, 2021). Similar findings were found in an American study that the majority of children were developmentally on track as a result of early childhood stimulation intervention (Rosenberg et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
“…Such services include clinic outreaches, home visits, and ECD centres, which are positively associated with observed early childhood development. Research from elsewhere has indicated that the presence of ECD centres, healthcare and clinic services, and parental engagement programs is associated with higher odds of child development status (Minh et al, 2017;Prado-Galbarro et al, 2021). Similar findings were found in an American study that the majority of children were developmentally on track as a result of early childhood stimulation intervention (Rosenberg et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
“…The development of this test has not only been a result of a bibliographic review from Bisquerra's theoretical model but also of the participation of experts and the opinions of the target population. Moreover, this is aligned with the recommendation for stakeholder collaboration in the measurement of socioemotional learning to be consistent, developmentally appropriate and culturally sensitive [38]. Furthermore, we evaluated the response processes and consequences of administering the test to verify that the scores were not biased in any way.…”
Section: Discussionmentioning
confidence: 83%
“…Despite these limitations, our findings are consistent with prior research and this study Cad. Saúde Pública 2023; 39 (12):e00112422 served to identify potential associations between inadequate early childhood development and alcohol consumption and tobacco use, as well as other contextual factors. Future work based on longitudinal studies should try to confirm these associations with inadequate early childhood development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that mothers and families need supportive environments to be able to provide opportunities that allow their children to fulfill their potentialities. The neighborhood environment has been identified as key for supporting families to overcome adversities that could constrain child development 3 , 12 , 13 . Neighborhood residential instability in childhood can contribute to the development of major depressive disorder and antisocial personality disorder 14 .…”
Section: Introductionmentioning
confidence: 99%